Sistem Informasi Transaksi Simpan Pinjam BUMDes Desa Pendem Berbasis Web - Zulkarnaen, Muhammad Fauzi; Artawan, Muhammad Rodik; Zaen, Mohammad Taufan Asri (Jurnal Ilmiah IKIP Mataram, 2023)
Badan Usaha Milik Desa (BUMDes) Desa Pendem is a engaged in savings and loans that have been run savings from to year. However, the proses is still done using conventional processes that exist in the BUMDes System is still member registration by filling out the registration from on the sheet, next to savings and loans are still recorded on the books recapitulation of loans and deposits. With the system is run to make the BUMDes management Desa Pendem to search member data becomes longer so that it will affect the efficiency of time and effort. Security and processing the acuracy of data doubt because it does not close the possibility of fraud is intentional or unintentional. In the study, researchers tried to analyze the problem issues that exist, and try to provide solutions for the management of information technology to be able to start development methods SDLC. Designing the process models using DFD models, database design, interface design and the relationships between tables. Generated application from of web-based applications â€œInformation System Savings and Loansâ€, so by using the information system of saving and loan BUMDes members faster, processing savings and loans become more easily and accurately, BUMDes members who wish to make a payment faster in the process as well as members of the BUMDes data search can be done quickly.